2023
DOI: 10.7150/ijbs.80140
|View full text |Cite
|
Sign up to set email alerts
|

FOXO3 regulates Smad3 and Smad7 through SPON1 circular RNA to inhibit idiopathic pulmonary fibrosis

Abstract: Forkhead box protein O3 (FOXO3) has good inhibition ability toward fibroblast activation and extracellular matrix, especially for the treatment of idiopathic pulmonary fibrosis. How FOXO3 regulates pulmonary fibrosis remains unclear. In this study, we reported that FOXO3 had binding sequences with F-spondin 1 (SPON1) promoter, which can activate its transcription and selectively promote the expression of SPON1 circRNA (circSPON1) but not mRNA expression. We further demonstrated that circSPON1 was involved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Several studies have demonstrated the critical role of circRNAs in the development and progression of IPF [ 7 9 , 12 , 13 ]. For example, Zhang et al found that circHIPK3 could promote lung fibroblast-to-myofibroblast transition by acting as a competing endogenous RNA of miR-338-3p, leading to increased SOX4 and COL1A1 expression [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated the critical role of circRNAs in the development and progression of IPF [ 7 9 , 12 , 13 ]. For example, Zhang et al found that circHIPK3 could promote lung fibroblast-to-myofibroblast transition by acting as a competing endogenous RNA of miR-338-3p, leading to increased SOX4 and COL1A1 expression [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al reported that circANKRD42 could sponge miR-324-5p and miR-136-5p to promote YAP1 translation into the nucleus during IPF [ 13 ]. Additionally, Li et al revealed that circSPON1 bound to miR-942-5p and miR-520f-3p, interfering with Smad7 mRNA and promoting Smad7 expression in the development of pulmonary fibrosis [ 7 ]. In our study, we found that hsa_circ_0044226 was positively associated with the lung function of IPF patients and upregulated in AE-IPF patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CircSPON1 generated from F-spondin 1 (SPON1) under the influence of forkhead box O3 (FOXO3) is involved in pulmonary fibrosis through the suppression of fibroblast activation by inhibiting the translocation of SMAD-3 into the nucleus. CircSPON1 also acts as a sponge for miR-942-5p and miR-520f-3p and increases the expression of SMAD-7 which regulates TGF-β signaling negatively [ 129 ]. Signal transducer and activator of transcription 3 (STAT-3) and zinc finger protein (Gli-2) are pro-fibrotic molecules which are involved in pulmonary fibrosis, and it was found that circRNA-662 and circRNA-949 have sponge like activity against miR-29b which interacts with STAT-3 and Gli-2.…”
Section: Regulatory Roles Of Circrnas In the Pathogenesis Of Ipfmentioning
confidence: 99%